Pengaruh Motivasi Karyawan Terhadap Kinerja Karyawan Di Pt. Xyz - Inriana Tiara Agnesia (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to find out the variables that affect the employee performances in PT. XYZ. The population consist of employee  of PT. XYZ using probability sampling method that of 127 respondents, 85 (67%) were male and 42 (33%) were women.. Data analysis using multiple regression analysis technique. The results of the testing of hypotheses shows that physical work environment, remuneration, status, social work environment, recognition, supervision, work itself, achievement has significant influence to employee performances.